1999
DOI: 10.1021/bi990766f
|View full text |Cite
|
Sign up to set email alerts
|

Core-Directed Protein Design. II. Rescue of a Multiply Mutated and Destabilized Variant of Ubiquitin

Abstract: We have applied the method described in the preceding paper [Finucane, M. D., et al. (1999) Biochemistry 38, 11604-11612], namely, stability-based selection using phage display, to explore the sequence requirements for packing in the hydrophobic core of ubiquitin. In contrast to the parent protein, which was a structurally compromised mutant, the selected variants could be overexpressed and purified in yields for structural studies. In particular, CD and NMR measurements showed that the selectants folded corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 51 publications
1
58
0
Order By: Relevance
“…11 As temperature is increased, however, the spectrum shifts to one that strongly resembles Ub. 12,13 The 231 nm minimum disappears, and the position and molar ellipticity of the new minimum are consistent with native Ub. The transition has a midpoint of ~30 ºC (Figure 2(b)) and is fully reversible upon cooling (not shown).…”
mentioning
confidence: 58%
“…11 As temperature is increased, however, the spectrum shifts to one that strongly resembles Ub. 12,13 The 231 nm minimum disappears, and the position and molar ellipticity of the new minimum are consistent with native Ub. The transition has a midpoint of ~30 ºC (Figure 2(b)) and is fully reversible upon cooling (not shown).…”
mentioning
confidence: 58%
“…First, the proteins in our system are potentially more exposed to proteolysis as they only have one fusion partner instead of two, and hence the selection may be more efficient; second, after selection, proteins can be expressed free from pIII and ready for characterization or large-scale production simply by changing the bacterial strain that is used (39).…”
Section: Discussionmentioning
confidence: 99%
“…low levels compared with WT-UBQ and was also totally lost in the protease selection studies (39). These properties provide good evidence that the AL 7 mutant was destabilized, although no direct stability measurement was possible.…”
mentioning
confidence: 95%
“…Although mutation of a handful of surface residues is conditionally lethal [6], the structure is remarkably resilient to core mutation, with the fold remaining intact when both overpacked and under-packed [10,11]. Experiments conducted on a F45W tryptophan mutant of ubiquitin, here referred to as the pseudo-wild type (WT*), revealed that hydrophobic-core mutations of WT* destabilise the protein, suggesting these residues might be conserved to maximise protein stability [12].…”
Section: Introductionmentioning
confidence: 99%